232The Impact of Australasian Voluntary Front of Pack Nutrition Labelling on Packaged Food Reformulation. (2nd September 2021) - Bablani, Laxman; Mhurchu, Cliona Ni; Neal, Bruce; Skeels, Christopher; Staub, Kevin; Blakely, Tony
Abstract: Background: Front-of-pack nutrition labelling (FoPL) of packaged foods can promote healthier diets. Australia & New Zealand (NZ) adopted the voluntary Health Star Rating (HSR) scheme in 2014. We studied the impact of voluntary adoption of HSR on food reformulation overall, and for more- versus less-healthy foods. Methods: Annual nutrition information panel data was collected for non-seasonal packaged foods sold in major supermarkets in Auckland from 2013-19, and Sydney from 2014-18. We used difference-in-differences to estimate reformulation associated with HSR adoption. Results: Healthier products adopted HSR more than unhealthy products: 35% of products that achieved four or more stars displayed the label compared to 15% of products that achieved two stars or less. Products that adopted HSR were 6.5% & 10.7% more likely to increase their rating by ≥ 0.5 stars in Australia and NZ, respectively. Labelled products showed a -4.2% [95% CI -6.5% to -1.9%] relative decline in sodium content in NZ, but there was no sodium change in Australia. There was a -2.3% [-3.7% to -1.0 %] change in sugar content in NZ and a -1.1% [-2.2% to 0.0%] difference in Australia. Initially unhealthy products showed larger reformulation when adopting HSR than healthier products. Conclusions: Overall, introduction of HSR had a small effect on product reformulation. The voluntary nature of the HSR program lowers effectiveness because labels were mostly placed on already healthy products. These already healthy products had limited scope for reformulation. Key messages: HSR adoption by unhealthy products should be incentivized, or mandated, by governments to maximise reformulation